tìm x
a,\(x^2+5x=6\)
b,\(x^2-2015x+2014=0\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
<=>(x2-x)-(2015x-2014)=0
<=>x(x-1)-2014(x-1)=0
<=>(x-2014)(x-1)
<=>x-2014=0
hoặc x-1=0
<=>x=2014
hoặc x=1
h
\(x^2-2015x+2014=0\)
\(\Leftrightarrow x^2-2014x-x+2014=0\)
\(\Leftrightarrow x\left(x-2014\right)-\left(x-2014\right)=0\)
\(\Leftrightarrow\left(x-1\right)\left(x-2014\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x-1=0\\x-2014=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=1\\x=2014\end{cases}}\)
\(x^2-2015x+2014=0\)
\(x^2-x-2014x+2014=0\)
\(x\left(x-1\right)-2014\left(x-1\right)=0\)
\(\left(x-1\right)\left(x-2014\right)=0\)
TH1:x -1 = 0
=>x=1
TH2 : x-2014=0
=> x=2014
\(x^3-4x=0\)
\(x\left(x^2-4\right)=0\)
\(x\left(x-4\right)\left(x+4\right)=0\)
TH1: x=0
TH2:x-4=0
=> x= 4
TH3: x+4=0
=> x=(-4)
Hok tốt
\(x^2-2015x+2014=0\)
\(x^2-2014x-x+2014=0\)
\(x\left(x-2014\right)-\left(x-2014\right)=0\)
\(\left(x-2014\right)\left(x-1\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x-2014=0\\x-1=0\end{cases}\Rightarrow\orbr{\begin{cases}x=2014\\x=1\end{cases}}}\)
\(x^2-2015x+2014\)\(=0\)
\(\Rightarrow x^2-x-2014x+2014\)\(=0\)
\(\Rightarrow x\left(x-1\right)-2014\left(x-1\right)\)\(=0\)
\(\Rightarrow\left(x-1\right)\left(x-2014\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x-1=0\\x-2014=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=1\\x=2014\end{cases}}\)
x^4-2014x^2+2015x-2014=0
<=>x4+x-2014x2+2014x-2014=0
<=>x.(x3+1)-2014.(x2-x+1)=0
<=>x.(x+1)(x2-x+1)-2014.(x2-x+1)=0
<=>(x2+x+1)[x.(x+1)-2014]=0
<=>x.(x+1)-2014=0 (vì x2+x+1 >0)
giải tiếp sao số xấu thế
a, x2+5x = 6
=> x2+5x - 6 =0
=> x2+6x -x- 6 =0
=> x(x+6)-(x+6)=0
=>(x-1)(x+6)=0
=> x=1 hoặc x=-6
b, x2-2015x +2014=0
=> x2-2014x-x +2014=0
=>x(x-2014)-(x-2014)=0
=> (x-1)(x-2014)=0
=> x=1 hoặc x=2014
k viết lại đề!
\(a.\\ \Leftrightarrow x^2+5x-6=0\\ \Leftrightarrow x^2+6x-x-6=0\\ \Leftrightarrow x\left(x+6\right)-\left(x+6\right)=0\\ \Leftrightarrow\left(x-1\right)\left(x-6\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}x-1=0\\x+6=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=1\\x=-6\end{matrix}\right.\\ \Rightarrow S=\left\{1;-6\right\}\)
\(b.\\ \Leftrightarrow x^2-2014x-x+2014=0\\ \Leftrightarrow x\left(x-2014\right)-\left(x-2014\right)=0\\ \Leftrightarrow\left(x-1\right)\left(x-2014\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}x-1=0\\x-2014=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=1\\x=2014\end{matrix}\right.\\ \Rightarrow S=\left\{1;2014\right\}\)